Generation of True Random TTL Signals for Quantum Key-Distribution Systems Based on True Random Binary Sequences - Salih, Salwa M.; Tawfeeq, Shelan K.; Khaleel, Ahmed I. (Iraqi Journal of Laser, 2019)
A true random TTL pulse generator was implemented and investigated for quantum key distribution systems. The random TTL signals are generated by low cost components available in the local markets. The TTL signals are obtained by using true random binary sequences based on registering photon arrival time difference registered in coincidence windows between two single – photon detectors. The true random TTL pulse generator performance was tested by using time to digital converters which gives accurate readings for photon arrival time. The proposed true random pulse TTL generator can be used in any quantum -key distribution system for random operation of the transmitters for these systems